Proceedings of the 52nd Annual Design Automation Conference 2015
DOI: 10.1145/2744769.2744923
|View full text |Cite
|
Sign up to set email alerts
|

Understanding soft errors in uncore components

Abstract: The effects of soft errors in processor cores have been widely studied. However, little has been published about soft errors in uncore components, such as memory subsystem and I/O controllers, of a System-on-a-Chip (SoC). In this work, we study how soft errors in uncore components affect system-level behaviors. We have created a new mixed-mode simulation platform that combines simulators at two different levels of abstraction, and achieves 20,000× speedup over RTL-only simulation. Using this platform, we prese… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Recent works combined an extremely detailed gate level fault injection in tandem with a faster (but still impracticable for complex devices) RTL evaluation [79], [103]. Cho et al used high level simulation (not using real hardware) triggering a RTL model when the fault needs to be injected [104]. Subasi et.…”
Section: Reliability Evaluation Methodologiesmentioning
confidence: 99%
“…Recent works combined an extremely detailed gate level fault injection in tandem with a faster (but still impracticable for complex devices) RTL evaluation [79], [103]. Cho et al used high level simulation (not using real hardware) triggering a RTL model when the fault needs to be injected [104]. Subasi et.…”
Section: Reliability Evaluation Methodologiesmentioning
confidence: 99%
“…It was examined that transient faults on the bus matrix could have severe consequences, possibly leading to deadlock, memory corruption, or undefined behavior [40,41]. A simulation study [42] observed the highest rate of erroneous application outcomes due to soft errors in the crossbar interconnect (only components external to the core underwent fault injection). This section provides a review of proposed and currently used bus protection approaches.…”
Section: Bus Protectionmentioning
confidence: 99%
“…Multi-objective genetic algorithm, based on gate sizing, is developed in [162] to optimize SER of standard cell circuits with marginal delay overhead. Recently in [163], soft error in non-core components such as memory and I/O subsystems is studied. A mixed mode simulation platform has been proposed to estimate how soft error in non-core components can affect the system level reliability.…”
Section: Soft Error Related Reliabilitymentioning
confidence: 99%